2006
DOI: 10.1111/j.1469-0691.2006.01353.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the use of RT-PCR for the early diagnosis of dengue fever

Abstract: RT-PCR was used to diagnose dengue virus infections confirmed serologically in 26 returning travellers. RT-PCR was positive for three (75%) of four samples taken on or before day 3 of the illness, for 15 (78.9%) of 19 samples taken between days 4 and 7, and for none of three samples tested on or after day 8 (p 0.0337). When applied early, RT-PCR seems to be a useful tool for the diagnosis of dengue fever.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…A recent study documented ongoing CHIKV transmission in Kwale County, south of Mombasa [7]. Laboratory diagnosis of CHIKV and DENV during acute phase of illness can be done through virus isolation or real-time reverse-transcription polymerase chain reaction (RT-PCR) [1113]. In a study by Riswari et al, CHIKV viremia preceded fever onset by up to six days, and CHIKV quantitative (qRT-PCR) testing on serial specimens indicated that viremia lasted for 11–13 days [14].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study documented ongoing CHIKV transmission in Kwale County, south of Mombasa [7]. Laboratory diagnosis of CHIKV and DENV during acute phase of illness can be done through virus isolation or real-time reverse-transcription polymerase chain reaction (RT-PCR) [1113]. In a study by Riswari et al, CHIKV viremia preceded fever onset by up to six days, and CHIKV quantitative (qRT-PCR) testing on serial specimens indicated that viremia lasted for 11–13 days [14].…”
Section: Introductionmentioning
confidence: 99%
“…Case identification has become increasingly important in the differential diagnosis of the acute febrile illnesses and hemorrhagic fever of unknown flavivirus infections during the early symptomatic phase. Currently, molecular techniques (reverse transcription-PCR [RT-PCR]) have widely replaced traditional virus isolation methods in the early detection of DENV infections and differentiation of the four DENV serotypes and other related flavivirus infections (12,21). Although molecular detection provides a promising sensitivity rate and rapid diagnosis, the molecular approach is costly, as it requires specialized laboratory equipment and experienced technicians; these are notable limitations in many developing countries where dengue disease is endemic (29).…”
mentioning
confidence: 99%
“…Also, there were no differences in the course of the disease in these patients. It is known that serum dengue IgM appears to peak about 2 weeks after the primary infection, declining to undetectable levels over 2-3 months whereas its persistence in CSF is about one month 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…PCR is usually positive in the first week of infection 20 . This test was negative in all of our cases probably due the longer time necessary to develop GBS after an infection; frequently more than one week.…”
Section: Discussionmentioning
confidence: 99%